Researches on the influence of slag addition and secondary treatment duration on steel quality. (February 2019) - Ardelean, E; Ardelean, M; Socalici, A; Puţan, V; Puţan, A
Abstract: Steel physical, mechanical and usage characteristics are influenced by its elaboration, secondary treatment, casting and further treatment. But if elaboration and secondary treatment do not benefit from the appropriate qualitative technological steps, it will not be possible to correct the resulting fails during the casting and processing stages. This paper introduces some laboratory researches related to the way steel quality can be influenced (in terms of sulphur and oxygen content) by the variation of the secondary treatment duration (inside the ladle) and that of the quantity of the reducing mixture in use (depending on the targeted metallurgical effect). The result consists in recommendable optimal variation intervals for the two parameters; these results can be easily implemented in industrial practice and therefore, with minimum costs, one can obtain maximal technological and economical effects.